An oil‐soluble extract of Rubus idaeus cells enhances hydration and water homeostasis in skin cells. (25th May 2015) - Tito, A.; Bimonte, M.; Carola, A.; De Lucia, A.; Barbulova, A.; Tortora, A.; Colucci, G.; Apone, F.
Synopsis: Objective: Raspberry plants, belonging to the species of Rubus idaeus, are known for their excellent therapeutic properties as they are particularly rich in compounds with strong antioxidant activity, which promote health and well‐being of human cells. Besides their high content of phenolic compounds, Rubus plants are rich in oil‐soluble compounds, which are also primary components of the hydrolipidic film barrier of the skin. As plant cell cultures represented a valuable system to produce interesting compounds and ingredients for cosmetic applications, we developed liquid suspension cultures from Rubus idaeus leaves and used them to obtain an active ingredient aimed at improving hydration and moisturization capacity in the skin. Methods: Rubus idaeus cells, grown in the laboratory under sterile and controlled conditions as liquid suspension cultures, were processed to obtain an oil‐soluble (liposoluble) extract, containing phenolic compounds and a wide range of fatty acids. The extract was tested on cultured keratinocytes and fibroblasts and then on the skin in vivo, to assess its cosmetic activities. Results: When tested on skin cell cultures, the extract induced the genes responsible for skin hydration, such as aquaporin 3, filaggrin, involucrin and hyaluronic acid synthase, and stimulated the expression and the activity of the enzyme glucocerebrosidase, involved in ceramide production. Moreover, the liposoluble extract increased the synthesis of the extracellular matrix components in cultured fibroblasts and showed a remarkable skin‐hydrating capacity when tested on human skin in vivo . Conclusions: Thanks to these activities, the Rubus idaeus liposoluble extract has several potential applications in skin care cosmetics: it can be used as hydrating and moisturizing ingredient in face and body lotions, and as anti‐ageing product in face creams specifically designed to fight wrinkle formation.